Representasi Tri Hita Karana pada Film Dokumenter 'Bali Menantang Masa Depan' - Indah Suryawati; Zahra Putri Suhada (Jurnal Pewarta Indonesia, 2025)
The documentary film ‘Bali Menantang Masa Depan’ by I Gede Putu Wiranegara contains opinions, social and cultural criticsm of the changes in Bali island since globalization. Bali is admired by people from within the country and abroad, because some of it is people still preserve their Balinese culture in the admist of modernization. The popularity of Bali has fatally led to corcens for it is natural condition and the condition of it is people. Researchers are interested in analyzing this film through the emergence of signs that are interpreted as part of the Balinese spiritual concept, Tri Hita Karana. This research uses Roland Barthes’s semantic thinking and analysis method, which divides the object of research into denotation, connotation, and myth. The results of the research are many problems that arise due to lack of maintining the pawongan. Nature still exist as it was formed and God will always remain with his nature, but mankind who change their nature. Keywords:  Documentary film; IGP Wiranegara; Bali; Tri Hita Karana; Semiotic; Roland Barthes; Modernization; Mankind; Pawongan.